Prolonged acute kidney injury exacerbates lung inflammation at 7 days post‐acute kidney injury. Issue 7 (22nd July 2014) - Andres‐Hernando, Ana; Altmann, Christopher; Bhargava, Rhea; Okamura, Kayo; Bacalja, Jasna; Hunter, Brandi; Ahuja, Nilesh; Soranno, Danielle; Faubel, Sarah
Abstract Patients with acute kidney injury (AKI) have increased mortality; data suggest that the duration, not just severity, of AKI predicts increased mortality. Animal models suggest that AKI is a multisystem disease that deleteriously affects the lungs, heart, brain, intestine, and liver; notably, these effects have only been examined within 48 h, and longer term effects are unknown. In this study, we examined the longer term systemic effects of AKI, with a focus on lung injury. Mice were studied 7 days after an episode of ischemic AKI (22 min of renal pedicle clamping and then reperfusion) and numerous derangements were present including (1) lung inflammation; (2) increased serum proinflammatory cytokines; (3) liver injury; and (4) increased muscle catabolism. Since fluid overload may cause respiratory complications post‐AKI and fluid management is a critical component of post‐AKI care, we investigated various fluid administration strategies in the development of lung inflammation post‐AKI. Four different fluid strategies were tested – 100, 500, 1000, or 2000 μL of saline administered subcutaneously daily for 7 days. Interestingly, at 7 days post‐AKI, the 1000 and 2000 μL fluid groups had less severe AKI and less severe lung inflammation versus the 100 and 500 μL groups. In summary, our data demonstrate that appropriate fluid management after an episode of ischemic AKI led to both (1) faster recovery of kidney function and (2) significantly reduced lung inflammation, consistent with the notion that interventions to shorten AKI duration have the potential to reduce complications and improve patient outcomes.